Fabrication of Nearly Hemispherical Polymer Lenses Using Water Droplets as Moulds. Issue 1 (2nd January 2016) - Karunakaran, Bhuvaneshwari; Jagirdar, Ammar; Paul, Debjani; Mukherji, Soumyo
ABSTRACT: In this paper, we present a novel method of fabricating nearly hemispherical polymer lenses using water droplets as moulds. Owing to the naturally forming meniscus of water, the surface of the lens is smooth. This technique allowed us to fabricate small lenses of diameter ∼1 mm, which makes them easy to integrate with lab-on-chip platforms. The focal length of the convex lenses was estimated to be ∼1 mm. Due to their hemispherical nature, these lenses have a high numerical aperture. The method is simple and cost effective as it eliminates the need for specialized and expensive equipment such as surface plasma cleaner. We fabricated both concave and convex lenses in polydimethylsiloxane (PDMS) using water droplets and PDMS lenses as moulds.